Social capital : second administrative reforms commission - India. Second Administrative Reforms Commission (New Delhi, 2008)
In this Report on Social Capital, the Commission has explored the evolution and growth of institutions that lie at the base of social capital in India; with particular reference to Societies, Trusts/ Charitable Institutions, Waqfs and Endowments, Voluntary Organisations at the grass roots levels such as Self-Help Groups, Self-Regulatory Authorities and Co-operatives. The Commission has examined these institutions in the context of their present legal underpinnings, their institutional designs, their interface with government and with other stakeholders; their respective roles and functions, their strengths and weaknesses and the reform agenda that should be charted out for these institutions. The recommendations made by the Commission spell out the changes required in the legal framework, as well as in the administrative structure and government policies to bring about independence, integrity, transparency, credibility and dynamism to these institutions.
Keywords: Societies and trusts